Severe ulcerative colitis during successful pregnancy. Issue 693 (July 1983) - Greenfield, C.; Pounder, R. E.; Craft, I. L.; Lewis, A. A.
Abstract : A 31-year-old patient presented with fulminant colitis during the 27th week of her first pregnancy. Despite failed medical treatment, colectomy was delayed because of the gravid uterus. A healthy child was delivered at 32 weeks by caesarian section, but a postoperative ileus appeared to induce transient colonic dilatation. A colectomy was performed 10 days post-partum. Both mother and child survived.